Dielectric and ferroelectric properties of lead magnesium niobate-lead zirconate titanate ceramics prepared by mixed-oxide method - Yimnirun R. (2014)
The dielectric and ferroelectric properties of (x)Pb(Mg1/3 Nb2/3)O3-(1 - x) Pb(Zr0.52 Ti0.48)O3 (where x = 0, 0.1, 0.3, 0.5, 0.7, 0.9, and 1.0) ceramics prepared by an oxide-mixing method are measured by means of an automated dielectric measurement set-up and a modified Sawyer-Tower circuit, respectively. The dielectric properties of the ceramics are measured as functions of both temperature and frequency. The results indicate that the dielectric properties of the pure-phase PZT and PMN are of normal and relaxor ferroelectric behaviors, respectively. The dielectric behaviors of the 0.1PMN-0.9PZT and 0.3PMN-0.7PZT ceramics are more of normal ferroelectrics, while the other compositions are obviously of relaxor ferroelectrics. In addition, the transition temperature decreases and the maximum dielectric constant increases with increasing PMN content in the system. The P-E hysteresis loop measurements demonstrate that the ferroelectric properties of the ceramics in PMN-PZT system change gradually from the normal ferroelectric behavior in PZT ceramic to the relaxor ferroelectric behavior in PMN ceramic. These results clearly show the significance of PMN in controlling the electrical responses of the PMN-PZT system. © 2004 Elsevier Ltd. All rights reserved.